Target-controlled in situ formation of G-quadruplex DNAzyme for a sensitive visual assay of telomerase activity. Issue 20 (23rd August 2019) - Wang, Yaocai; Yang, Luzhu; Wang, Yanjun; Liu, Wei; Li, Baoxin; Jin, Yan
Abstract : A sensitive visual assay was developed for detecting telomerase activity based on the telomerase-controlled in situ formation of G-quadruplex-hemin DNAzyme. The telomerase activity of 5 HeLa cells per μL was visually detected in human serum. Abstract : It is of great importance to achieve facile and reliable detection of telomerase because it is an important cancer biomarker. The complex components of cell extracts and ultra-low concentration of telomerase makes it more difficult to realize a simple and sensitive visual detection of telomerase activity. Herein, a facile and sensitive visual strategy was developed for the detection of telomerase based on the telomerase-controlled in situ formation of a G-quadruplex-hemin DNAzyme. To avoid the influence of the complex components of cell extracts, a telomerase substrate (TS) was immobilized onto the surface of magnetic beads (MBs) to form a MB/TS complex. MB/TS incubated with telomerase can add several TTAGGG repeat units to the 3′ terminal of TS. After magnetic separation and washing, these G-rich elongated DNA folded into numerous G-quadruplex-hemin DNAzymes under the aid of K + and hemin, which efficiently catalysed the TMB/H2 O2 reaction. Magnetic separation basically eliminated the non-specific background interference from other cell extracts and redundant hemin. Taking full advantage of the in situ formation of multiple catalysts, the telomerase activity could be sensitively evaluated by a color change of the TMB/H2 O2 solution. The telomerase activity down to 1 HeLa cell per μL and 0.5 HeLa cell per μL can be measured by the naked eye and UV-vis spectroscopy, respectively. Due to the magnetic separation and enrichment, the sensitivity was obviously improved compared with the previous colorimetric assay. Meanwhile, the telomerase activity of 5 HeLa cells per μL in human serum can be visually detected. Therefore, this study provides a facile, cost-effective and robust colorimetric assay for the visual detection of telomerase activity, which holds great potential in telomerase-based cancer clinical diagnostics.